2015
DOI: 10.1002/pbc.25783
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Follow‐Up in Survivorship as a Standard of Care in Pediatric Oncology

Abstract: Childhood cancer survivors (CCS) have a high risk of medical late effects following cancer therapy. Psychosocial late effects are less often recognized. Many CCS do not receive long-term follow-up (LTFU) care, and those who do are rarely screened for psychosocial late effects. An interdisciplinary team conducted a systematic review of qualitative and quantitative studies to assess social, educational, vocational, psychological, and behavioral outcomes along with factors related to receipt of LTFU care. We prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
113
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(129 citation statements)
references
References 185 publications
8
113
1
2
Order By: Relevance
“…With regard to clinical implications, regular screening for anxiety and related symptoms should be implemented in survivorship clinics in accordance with the standards of psychosocial care for children with cancer and their families(41, 42). Screening is particularly important in this population, as one study(36) found that adolescents did not volunteer information regarding concerns about sensitive topics, such as fertility, unless directly asked.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to clinical implications, regular screening for anxiety and related symptoms should be implemented in survivorship clinics in accordance with the standards of psychosocial care for children with cancer and their families(41, 42). Screening is particularly important in this population, as one study(36) found that adolescents did not volunteer information regarding concerns about sensitive topics, such as fertility, unless directly asked.…”
Section: Discussionmentioning
confidence: 99%
“…2,10 Some, particularly those treated with cranial radiation, experience social isolation and struggle in school and the workplace. 5,6,[11][12][13] Thus the practice of LTF care has grown at pediatric oncology centers in recent decades.…”
mentioning
confidence: 99%
“…screening for pediatric cancer survivors on an annual basis 39 , and that psychosocial follow-up in pediatric cancer survivors is one of 15 standards of care in pediatric psychosocial oncology 1 , both child and parent reports of child hrql should be obtained during routine screenings. Our findings indicate that particular attention should be paid to the hrql of survivors who are experiencing psychosocial family risks, female survivors, and for survivors who have experienced higher levels of treatment intensity, as these children are at the highest risk of poor hrql.…”
Section: Discussionmentioning
confidence: 99%
“…Survival rates for childhood cancer have improved dramatically in recent years as a result of rapid advancements in treatments 1,2 . Given this growing population of survivors, attention has been increasingly placed on adjustment and health-related quality of life (hrql) as children move from treatment into survivorship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation